To eliminate y, double the second equation and add it to the first.

2(3x + 2y) + (2x - 4y) = 2(18) + (-4)

8x = 32

x = 4

You can solve for y by substituting this value into either equation.

2(4) - 4y = -4

12 - 4y = 0

3 - y = 0

3 = y

2(3x + 2y) - 3(2x - 4y) = 2(18) - 3(-4)

6x + 4y - 6x + 12y = 36 + 12

16y = 48

y = 3

2(3x + 2y) + (2x - 4y) = 2(18) + (-4)

8x = 32

x = 4

You can solve for y by substituting this value into either equation.

2(4) - 4y = -4

12 - 4y = 0

3 - y = 0

3 = y

##### The solution is (x, y) = (4, 3).

You can eliminate x by multiplying the first equation by 3 and subtracting that from twice the second equation. The idea of doing the multiplications is to make the coefficients of the x terms in the product be the same. Then, when you do the subtraction, they cancel.2(3x + 2y) - 3(2x - 4y) = 2(18) - 3(-4)

6x + 4y - 6x + 12y = 36 + 12

16y = 48

y = 3